(untitled) (Journal of human and social sciences, 2015)
This paper explores the importance of studying contract nullifiers in Islamic jurisprudence, focusing on usury (riba), uncertainty (gharar), and unlawful appropriation of wealth. It discusses the varying degrees of corruption and their effects, providing practical examples from contemporary issues. The study also addresses exceptions and dispensations in certain void contracts.